DETERMINATION OF URINARY CONCENTRATIONS OF ORGANIC SOLVENT IN URBAN WORKERS - Reza Ahmadkhaniha; Masud Yunesian; Maryam Zare-Jeddi; Noushin Rastkari (Journal of Air Pollution and Health, 2015)
Introduction: Concerns about indoor air quality have drawn researcher’s attention in the last years. This becomes more important with knowledge of that 90% of people’s daily times are spent inside the home and workplaces. Solvents are an example of prevalent hazard chemical, which are less-studied comparing pesticides or metals. Chlorinated solvents such as carbon tetrachloride, chloroform, and dichloromethane constitute an important class of solvent, which applies for a variety of consumer and industrial cleaning purposes especially in the laboratory. Mentioned components represent various side effects and carcinogenic implication that could adversely affect workers exposed to solvents. Materials and Methods: In the present study the excretion of urinary carbon tetrachloride, chloroform, and dichloromethane were evaluated as biomarkers of exposure to chlorinated solvents. With this aim, forty chemistry laboratory technicians from several universities in Tehran and forty occupationally non-exposed persons were investigated. Spot urine samples were obtained prior to and at the end of the work shift from each subject. The urinary levels of chlorinated solvents were determined by using headspace gas chromatography and mass spectrometry detection. Results: The mean concentrations of chloroform and dichloromethane in chemistry laboratory technicians were significantly greater than the control groups. Although the mean levels of carbon tetrachloride before the work shift in technicians were higher than the occupationally non-exposed group, a statistically significant difference could not be observed (Pvalue= 0.324). Conclusions: The results showed that the laboratory technicians are one of the most exposed groups among occupationally exposed people with the main route of exposure through inhalation.